A Model for Evaluating the Solution Space of Mass Customization Toolkits - Hermans, Guido (International Journal of Industrial Engineering and Management, 2012)
Mass customization involves consumers in the design process by enabling them to customize a product through the use of a toolkit. The aim of this paper is to develop a profound understanding of constructing a solution space of mass customization toolkits and to examine the autonomy of the user in relation to the solution space. In this study a model is proposed that can be used to evaluate the solution space of mass customization toolkits. The model is based on target outcome and guidance and analyses toolkits by examining product attributes, mechanisms and choice in the solution space and guidance throughout the process of customization. The three main findings presented concern the emphasis of existing toolkits on customizing ‘hard’ product attributes, a strong focus on ‘lower-level’ product attributes, and the lack of uniqueness in the outcomes from current toolkits. Article history: Received (19 November 2012); Revised (02 December 2012); Accepted (06 December 2012)